Green Synthesis, Characterization and Larvicidal Activity of Cu/Ni Bimetallic Nanoparticles Using Fruit Extract of Palmyra Palm - Danbature, Wilson Lamayi; Shehu, Zaccheus; Mai, Abigail John; Magaji, Buhari; Adam, Muhammad Mustapha; Bunu, Musa Aminu (International Journal of Chemistry and Materials Research, 2020)
The mixture of Cu2+/Ni2+ solution was reduced to Cu/Ni BMNPs using fruit extract of Palmyra palm as a green reducing agent. The formation of Cu/Ni BMNPs noticed based on the visual change in color of the reaction mixture at room temperature from sky-blue to light blue within 15 min. UV-Visible and Fourier Transform Infra Red spectrophotometers were applied to investigate the Optical properties as well as the interaction between the formed Cu/Ni hybrid nanoparticles and the raw fruit extract respectively. These Cu/Ni BMNPs were evaluated for larvicidal potency against first, second and third instars of Culex quinquefasciatus. The larvicidal studies were carriedout at the concentration range of 5-50 mg/L (Cu/Ni BMNPs) and the %mortality increases with increase in concentration for all the instars. The result showed good activity where the lethal concentration values herein for the three instars were LC50=14.75, LC90=83.96; LC50=18.25, LC90=258.83; LC50=18.50, LC90=331.50 mg/L respectively. Therefore, Cu/Ni BMNPs could be a potential future nanolarvicide for Culex quinquefasciatus.